(untitled) (Psychology Travelogs, 2023)
The purpose of the article is to analyze and compare various theoretical descriptions and interpretations of the concept of post-traumatic stress disorder, its main components and approaches to therapy. In the conditions of martial law, in which our state is now, its citizens are exposed to a significant influence of various stress factors. This leads to the maladjustment of the individual in society, the complication or complete break of relations with relatives, friends, colleagues, emotional and physical exhaustion. In addition, PTSD can become one of the prerequisites for the development of other mental pathologies, such as depression, anxiety disorder, alcoholism, etc. It is important to distinguish post-traumatic stress disorder from acute stress disorder. To diagnose PTSD, it is important to use both standardized test questionnaires and an interview with the victim. It is important not to neglect the psychological enlightenment of the victims. Among the methods and forms of psychotherapy for people with PTSD, it is worth using group therapy, trauma-focused cognitive-behavioral therapy, EMDR. For a successful diagnosis, PTSD it is necessary to use standardized methods and individual diagnostic conversations with the patient. During therapy, it is necessary to pay attention to the elimination of symptoms of avoidance of triggers and traumatic memories. In our opinion, there is a need to expand the spectrum of methods of social and psychological rehabilitation of PTSD victims, which can become the basis for further research.